2021
DOI: 10.1161/circulationaha.120.052009
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles From Epicardial Fat Facilitate Atrial Fibrillation

Abstract: Background: The role of epicardial fat (eFat)-derived extracellular vesicles (EVs) in the pathogenesis of atrial fibrillation (AF) has never been studied. We tested the hypothesis that eFat-EVs transmit proinflammatory, profibrotic, and proarrhythmic molecules that induce atrial myopathy and fibrillation. Methods: We collected eFat specimens from patients with (n=32) and without AF (n=30) during elective heart surgery. eFat samples were grown as organ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 70 publications
1
103
0
1
Order By: Relevance
“…Bioinformatics analysis showed that these miRNAs and their targets possibly contribute to atrial fibrosis (11). Moreover, it has been demonstrated that, compared with the control group, the epicardial adipose tissue of patients with AF secretes more exosomes, and the expression of pro-inflammatory and pro-fibrotic factors is higher in exosomes (12). In addition, a recent study reported that myofibroblast-derived exosomes reduced the expression of voltage-gated L-type calcium channel subunit α1c (Ca v 1.2) and increased the vulnerability to AF (13).…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics analysis showed that these miRNAs and their targets possibly contribute to atrial fibrosis (11). Moreover, it has been demonstrated that, compared with the control group, the epicardial adipose tissue of patients with AF secretes more exosomes, and the expression of pro-inflammatory and pro-fibrotic factors is higher in exosomes (12). In addition, a recent study reported that myofibroblast-derived exosomes reduced the expression of voltage-gated L-type calcium channel subunit α1c (Ca v 1.2) and increased the vulnerability to AF (13).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a unique molecular footprint has recently been shown in EAT from AF subjects. In particular, EAT derived extracellular vesicles (EVs) exert profibrotic/proinflammatory effects on the neighboring atrial tissue, promoting arrhythmogenesis [ 71 ]. In addition, EAT expansion seems to be positively regulated through increased atrial natriuretic peptide (ANP) levels [ 72 ].…”
Section: Atrial Fibrillation Pathogenesismentioning
confidence: 99%
“…Subsequently, we discussed the pros and cons of the use of exosomes. The application of exosomes has many advantages (32,193,230): (1) Alterations in exo-cargoes profile secreted by cardiac cells during AF would reflect the parental cells pathophysiological state with extreme specificity and sensitivity, and therefore they may appear as "fingerprint" of the AF pathogenetic processes; (2) Exosomes can be isolated from nearly all obtainable biofluids such as blood and urine; (3) Exosomes serve as a vehicle that protects cargoes from degradation and targets the cargoes to the recipient cells, with the less traumatic and abnormal modifications. (4) Welldesigned engineered exosomes may enhance their therapeutic effects, making them promising tools for clinical application.…”
Section: Advantages and Disadvantages Of Exosome For Afmentioning
confidence: 99%